2012
DOI: 10.1007/s00268-012-1502-7
|View full text |Cite
|
Sign up to set email alerts
|

Breast Abscess, an Early Indicator for Diabetes Mellitus in Non‐lactating Women: A Retrospective Study from Rural India

Abstract: This study shows that DM can present as breast abscess in non-lactating women. Therefore, non-lactating women with a breast abscess should be evaluated for DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…2 A foreign study found that non-puerperal mastitis is more prevalent in women aged 26 to 45, with an average age of 35.5 years. 3 The disease mainly affects young and middle-aged women, with fewer cases in adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…2 A foreign study found that non-puerperal mastitis is more prevalent in women aged 26 to 45, with an average age of 35.5 years. 3 The disease mainly affects young and middle-aged women, with fewer cases in adolescents.…”
Section: Introductionmentioning
confidence: 99%